2019
DOI: 10.21511/ppm.17(1).2019.33
|View full text |Cite
|
Sign up to set email alerts
|

Methodology of national investment and innovation security analytics

Abstract: The main problem of the research is development of a conceptual framework for investment and innovation security, as well as the methodological approach to its assessment, which will allow monitoring and identifying the threats and achieving the desired security state of the national economy. It has been proved that investment and innovation security is a multi-level phenomenon, consisting of the following levels: global, national, corporate and household ones. Investment and innovation security is determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The analysis of the activities of domestic and foreign venture capital companies and literary sources, carried out by the authors, showed that it is not enough to use only known financial indicators to assess the effectiveness of the use of venture capital in the implementation of an innovative project in construction (Prokopenko et al, 2019). In this case, an integrated approach is required.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the activities of domestic and foreign venture capital companies and literary sources, carried out by the authors, showed that it is not enough to use only known financial indicators to assess the effectiveness of the use of venture capital in the implementation of an innovative project in construction (Prokopenko et al, 2019). In this case, an integrated approach is required.…”
Section: Resultsmentioning
confidence: 99%
“…During the whole period of Ukrainian independence, the taxation system was imperfect. Many authors stressed that Ukraine's taxation system needs to be deeply reformed, and significant tax structure changes must be taken (Prokopenko et al, 2019;Zakharkin et al, 2019). The vertical transfers system should be limited to the amounts of benefits granted under the insurance contributions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on our previous research [15][16] and studies [17; 18], we propose a methodology for analytical support of innovation and technological changes management through the development of integrated development strategies within the national development strategies. This methodology is based on necessity of identifying the mechanisms based on maximizing the relationship between the technological paradigm and the cross-industry technological trajectory.…”
Section: Sector Innovation Development Models Composition Frameworkmentioning
confidence: 99%